'Jaw-in-a-Day' simultaneous jaw reconstruction with intraoral implant surgery. (October 2021) - Shin, S.
Abstract : Purpose: Composite defects including teeth-soft tissue-bone are caused after tumor ablation in oral and maxillofacial area and makes severe problems in diet and phonation. There have been some trials to reconstruct occlusion immediately after tumor ablation. Max et al. reported fibula reconstruction with CAD/CAM reconstruction plates and dental implants. They reported a fibula cutting guide which has holes for dental implant position. Yadranko et al. reported a 3d printed mandible model to simulated fibula segment fixation and dental implant installation. Here we report a technique using a teeth supported dental implant guide to reconstruct proper occlusion immediately. Methods: Previous reported articles were reviewed. Comparison between installing implants several years after reconstruction was done. According to reports of Max et al., there were 3.3 mm centerpoint deviation and 13.0 degree angular deviation of implant with their Methods. Results: Reconstructing occlusion simultaneously with bone has several advantages. It dramatically shortens period of dentition loss. Soft tissue management can be done simply. In result, when installing dental implants outside the oral cavity, error due to bone positioning is inevitable. Intraoral implant surgery after fixation of bone segment is thought to reduce these errors. Conclusions: Our final goal for reconstruction of oral and maxillofacial defect is not positioning bone segment properly but reconstructing proper occlusion. Even though the bone segment is positioned in a slightly different position from the planned position, intraoral implant guide using other teeth as a reference will make it possible to install implant in planned position.